Studi Tentang Modifiedn Packing Order di Bursa Efek Indonesia - Surwanti, Arni (Universitas Muhammadiyah Yogyakarta, 2011)
This study examines whether there is market reaction to the presence of external financing decisions on companies in the Indonesia Stock Exchange under the Modified Theory pecking order, while also testing whether there is a diffeence between the market reaction to the interval in the period of observation of the external funding decisions at the company in the Indonesia Stock Exchange. This study uses object manufacturing companies listing on the Indonesia Stock Exchange in the period of 2005-2008. The company studied is a company that in the period of 2005-2008 to the acquistion of external funding sources have either a long-term debt financing and issuance of new shares. Companies that observed in this study were 58 companies, whit a 4-year observation period, cansisting of 20 companies to issue new share during the observation periode showed a positive abnormal return. The average abnormal return the company to abtain long-term debt financing during the observation periode showed a positive abnormal return. Based on the different test result on average only on testing the market reaction to companies that meet emission requisition of shares of the fund sources indicate the probability that reflects differences in market reaction to companies that meet the funding requirements by emission of shares at 5 days before and 5 days after that announcement of issuance of new shares.